Single Photon Detection Technology in Underwater Wireless Optical Communication: Modulation Modes and Error Correction Coding Analysis - Gai, Lei; Li, Wendong; Wang, Guoyu (Journal of Ocean University of China, 2024)
This study explores the application of single photon detection (SPD) technology in underwater wireless optical communication (UWOC) and analyzes the influence of different modulation modes and error correction coding types on communication performance. The study investigates the impact of on-off keying (OOK) and 2-pulse-position modulation (2-PPM) on the bit error rate (BER) in single-channel intensity and polarization multiplexing. Furthermore, it compares the error correction performance of low-density parity check (LDPC) and Reed-Solomon (RS) codes across different error correction coding types. The effects of unscattered photon ratio and depolarization ratio on BER are also verified. Finally, a UWOC system based on SPD is constructed, achieving 14.58 Mbps with polarization OOK multiplexing modulation and 4.37 Mbps with polarization 2-PPM multiplexing modulation using LDPC code error correction.